Geographical disparity and traumatic brain injury in America: Rural areas suffer poorer outcomes (2019)
Significant heterogeneity exists in traumatic brain injury (TBI) outcomes. In the United States, TBI remains a primary driver of injury‐related mortality and morbidity. Prior work has suggested that disparity exists in rural areas; our objective was to evaluate potential differences in TBI mortality across urban and rural areas on a national scale. Methods: Age‐adjusted TBI fatality rates were obtained at the county level across the U.S. from 2008 to 2014. To evaluate geography, urban influence codes (UIC) were also obtained at the county level. UIC codes range from 1 (most urban) to 12 (most rural). Metropolitan counties are defined as those with an UIC ≤2, while nonmetropolitan counties are defined as an UIC ≥3. County‐level fatality rates and UIC classification were geospatially mapped. Linear regression was used to evaluate the change in TBI fatality rate at each category of UIC. The median TBI fatality rate was also compared between metropolitan and nonmetropolitan counties. Results: Geospatial analysis demonstrated higher fatality rates distributed among nonmetropolitan counties across the United States. The TBI fatality rate was 13.00 deaths per 100,000 persons higher in the most rural UIC category compared to the most urban UIC category (95% confidence interval 12.15, 13.86; P < 0.001). The median TBI rate for nonmetropolitan counties was significantly higher than metropolitan counties (22.32 vs. 18.22 deaths per 100,000 persons, P < 0.001). Conclusions: TBI fatality rates are higher in rural areas of the United States. Additional studies to evaluate the mechanisms and solutions to this disparity are warranted and may have implications for lower‐and middle‐income countries.